EFEK VARIASI LUBANG INJEKTOR TERHADAP EMISI GAS CO DAN HC: EFFECT OF INJECTOR HOLE VARIATIONS ON CO AND HC GAS EMISSIONS - Dwi, Muhammad Dwi Pangestu; Ahmad Hanif (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2025)
Motorcycles are the most widely used vehicles in Indonesia due to their practicality, especially those with automatic transmissions. However, the increasing number of motorcycles, particularly in East Java Province, has contributed significantly to air pollution through exhaust gas emissions. This study aims to analyze the effect of injector hole variation and fuel octane rating (RON) on exhaust emissions and in 110cc gasoline motorcycles. The method involves laboratory testing with injector hole variations (4, 6, 8, 10) and the use of Shell RON 92 and RON 95 fuels. The observed variables include exhaust emissions (CO and HC) and specific fuel consumption, with engine temperature controlled at 80–85°C and fuel pressure at 43 psi. The results show that the configuration of a 6-hole injector with RON 95 produces the lowest emission values, with CO at 0.02% and HC at 84 ppm, meeting the Indonesian Ministry of Environment and Forestry’s emission standards (CO ≤ 3%, HC ≤ 1000 ppm), while also achieving the most efficient fuel consumption across all RPM ranges.